OJEK PANGKALAN VERSUS OJEK ONLINE (PEMBERDAYAAN BERBASIS KOMUNITAS DAN KETAHANAN EKONOMI OJEK PANGKALAN) - Fathy, Rusydan (P2KK LIPI, 2018)
Technology has penetrated into the transportation services sector in Indonesia. The existence of application-based ojek is a manifestation of technology adaptation into the transportation services sector. Its emergence replacing the ojek pangkalan’s existence as an alternative transportation. For members of ojek pangkalan who are able to adapt, they choose to become ojek online’s driver, while those who do not, choose to survive. However, the inability to adapt is getting worse with weakening the quality of their social capital. Ojek pangkalan’s entity as a community currently has a negative image in society because of their poor quality management system. This paper exploring community-based empowerment of ojek pangkalan and their economic resilience. This paper was conducted using qualitative approach. Data analyzed through the three-stage data encryption technique: open code, axial code and selective code. Arguments are formulated through analysis using social capital theory as a main theoretical framework. The opening of this article placing ojek pangkalan’s entity into the macro domain of urban studies. Ojek pangkalan will be drawn into the context discussion of a community. The main part of this article is exploring the social capital that Ojek Pangkalan Salemba have, which is the process of the establishment and how its role in making of economic resilience. Besides that, for the closing part, this article describe the constellation of ojek pangkalan’s existence in context of community-based empowerment.